2022
DOI: 10.1172/jci.insight.146243
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast YAP/TAZ activation is a key step in organ fibrogenesis

Abstract: Fibrotic diseases account for nearly half of all deaths in the developed world. Despite its importance, the pathogenesis of fibrosis remains poorly understood. Recently, the two mechanosensitive transcription cofactors YAP and TAZ have emerged as important profibrotic regulators in multiple murine tissues. Despite this growing recognition, a number of important questions remain unanswered, including which cell types require YAP/TAZ activation for fibrosis to occur and the time course of this activation. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 66 publications
(100 reference statements)
0
25
0
Order By: Relevance
“…In this retrospective case control study, we analyzed a convenience sample of 18 archived human transplant kidney biopsies stored in the Department of Laboratory Medicine and Pathobiology at St. Michael’s Hospital ( 57 ). The inclusion criteria were as follows: (i) Kidneys must have been transplanted >1 year prior, and (ii) sufficient tissue is needed to be available for RNA-seq.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this retrospective case control study, we analyzed a convenience sample of 18 archived human transplant kidney biopsies stored in the Department of Laboratory Medicine and Pathobiology at St. Michael’s Hospital ( 57 ). The inclusion criteria were as follows: (i) Kidneys must have been transplanted >1 year prior, and (ii) sufficient tissue is needed to be available for RNA-seq.…”
Section: Methodsmentioning
confidence: 99%
“…Details of data collection are provided in the Supplementary Materials. RNA sequencing RNA was extracted from kidney biopsy tissue, and complementary DNA (cDNA) libraries were prepared and sequenced on an Illumina HiSeq 2000 or 3000 (57), as described in the Supplementary Materials. RNA yield, read numbers per sample, and other relevant data are summarized in table S4.…”
Section: Human Kidney Biopsy Studymentioning
confidence: 99%
“…However, verteporfin treatment inhibited TGF-βinduced Smad activation and thereby impaired UUO-induced renal fibrosis and fibroblasts activation in cultured cells [17]. Myofibroblast-specific ablation of YAP/TAZ attenuated kidney fibrosis, while myofibroblast-specific deletion of LATS1 and LATS2 promoted YAP/TAZ activation in myofibroblasts and aggravated fibrosis [40].…”
Section: Hippo Signaling Pathway In Renal Fibrosismentioning
confidence: 98%
“…As such, treatment of mice with an MST1/2 blocker XMU-MP-1 inhibits pressure-induced cardiac hypertrophy and fibrosis (Table 1) [39]. Similarly, LATS1/2-mutant cardiac fibroblasts are less prone to develop into fibrotic phenotype after infarction-induced injury [35], while deletion of LATS1/2 stimulates YAP/TAZ activation in myofibroblasts and aggravates kidney fibrosis [40]. Similarly, genetic inactivation of SAV1 in renal tubule cells promotes renal interstitial fibrosis [36].…”
Section: Introductionmentioning
confidence: 99%
“…Yes-associated protein (YAP), an effector of the canonical Hippo signaling pathway, can be activated by upstream mechanical signals (such as the increase in matrix stiffness), which promotes its nuclear translocation and targeted gene induction, and has emerged as a crucial factor in the pathogenesis of fibrosis in organs, including the kidney, liver, lung and cardiac tissue (Hu et al, 2021). A recent report confirmed that myofibroblast YAP was activated early and driven to fibrosis in the liver, lung and kidney injury in mice and humans (He et al, 2022). However, although we had profound insights into fibrosis at the cellular and molecular level, and had built different pathogenic models to mimic fibrogenesis, there were few satisfactory therapies and even fewer approaches focusing on mechano-regulation in clinical practice.…”
Section: Introductionmentioning
confidence: 99%